Evaluation of the effect of acupuncture on weight loss in postpartum obese women: a study protocol for a randomized controlled trial - Han Zhang; Xinyu Zhang; Yuejiao Wang; Ran Yang; Yanan Zhen; Yang Zhang; Qi Zhao; Yinping Xu; Zhishun Liu; Shulan Wang (Contemporary Clinical Trials Communications, 2025)
Background: Pregnant women gain an average weight of 16.6 ± 4.8 kg during pregnancy, with weight retention of 4 kg at 6 months, 4 kg at 12 months, and 2.9 kg at 18 months postpartum. At 3, 6, 9 and 12 months after delivery, 61.92 %, 68.73 %, 78.18 % and 84.24 % of women whose BMI returned to the normal range, respectively. Obesity has negative effects on postpartum women's physical and mental health. Prior research has suggested that acupuncture may be beneficial for weight loss. This study investigates the effectiveness of manual acupuncture (MA) for treating postpartum obesity (PO), compared to sham acupuncture (SA). Methods: This is a multicenter, randomized, single-blind controlled trial. A total of 82 eligible PO participants will be randomly assigned to either MA (n = 41) or SA (n = 41) group using a 1:1 ratio. The MA group received acupuncture treatment and the control group received sham acupuncture treatment. Both groups received diet and exercise instructions and were treated for 30 min each session, three times a week, for a total of 8 weeks. The primary outcome measure was the change in body mass index (BMI) after 8 weeks of treatment, compared to baseline. Secondary outcome measures include changes in BMI from baseline to 4 weeks of treatment, changes in waist circumference, waist-to-hip ratio (WHR), blood glucose, lipid levels, thyroid function and other serological measures from baseline to 8 weeks of treatment. Secondary measures also included dietary and exercise guidance compliance scales, as well as assessments of depression and anxiety status. The safety of acupuncture was continuously evaluated throughout the study. Follow-up was performed at 14 and 20 weeks after treatment. Discussion: This prospective randomized trial will help evaluate the efficacy and safety of acupuncture in treating PO. The results of this study will provide evidence of the therapeutic effectiveness of acupuncture on PO. Trial registration: chictr.org.cn: ChiCTR2300067658, registered on January 17, 2023.